Methodologic Considerations in the Evaluation of Opioids and Medical Cannabis for Chronic Pain - Noori, Atefeh (My University, 2021)
Opioids are commonly prescribed for chronic pain, particularly in North America; however, growing awareness of their modest benefits and risk of serious harms has raised concerns whether their wide-spread use is evidence-based. Moreover, there are multiple opioids available for use, including both short-acting and sustained-release formulations, and their comparative effectiveness for chronic pain has not been established. It remains possible that some types of opioids may be associated with greater net benefits than others. The first chapter of my thesis presents the results of a network meta-analysis that explores the relative effectiveness of opioids available for the management of chronic non-cancer pain. The strength of inferences from the results of network meta-analyses depends on the certainty of the evidence, and different approaches are available to make this appraisal. The second chapter of my thesis explores the concordance of two approaches for assessing the certainty of evidence from network meta-analyses, the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) working group system, and the Confidence in Network Meta-Analysis (CINeMA) approach. Concerns over increasing rates of opioid-related overdose and death have generated enthusiasm for reducing opioid dose among chronic pain patients managed with long-term opioid therapy. My third chapter presents a systematic review of the impact of medical cannabis on opioid use among people living with chronic pain.